Ibrutinib treatment via alternative administration in a patient with chronic lymphocytic leukemia and dysphagia. (July 2021) - DiSogra, Kristyn Y; Tran, Thuy; Arnall, Justin R; Janes, Amanda; Moore, Donald C; Park, Steven I
Introduction: Ibrutinib is a small molecule inhibitor of Bruton's tyrosine kinase indicated for the treatment of a variety of B-cell malignancies including chronic lymphocytic leukemia, mantle cell lymphoma, marginal zone lymphoma, and Waldenstrom's macroglobulinemia. These indolent hematologic malignancies are considered diseases of the elderly, a population that may have dysphagia leading to difficulty swallowing tablets and capsules. Ibrutinib is currently not available in a liquid oral dosage form. We report the utilization and clinical outcomes associated with alternative administration of ibrutinib capsules in a patient with chronic lymphocytic leukemia and significant dysphagia. Case report: An 86-year old female requiring chronic lymphocytic leukemia-directed therapy due to a rising absolute lymphocyte count and worsening, transfusion-dependent anemia with a past medical history of dementia and dysphagia, was initiated on ibrutinib. Management & outcome: Due to the patient's significant inability to swallow, ibrutinib capsules were administered via an alternative method by opening them and sprinkling onto soft food or applesauce. With ibrutinib therapy, the patient has had a significant clinical response in her chronic lymphocytic leukemia as evidenced by her decreased absolute lymphocyte count and achieving transfusion independence with improvements in hemoglobin. Discussion: Ibrutinib administration via this alternative method resulted in an initial clinical response in the treatment of our patient's chronic lymphocytic leukemia as evidenced by a decreasing absolute lymphocyte count and improved anemia that achieved transfusion independence. The patient has maintained this response to therapy after approximately 1 year at the time of manuscript preparation.